'Ay, ay, divil, all's raight! We've smashed 'em!': Translating Violence and 'Yorkshire Roughness' in Charlotte Brontë's Shirley. (2nd January 2019) - Franklin, Sophie
Abstract : By taking Yorkshire Luddism as Shirley 's (1849) framework, Charlotte Brontë places political violence at the centre of its narrative. Despite this, much of the novel's inclusions of violence are largely undescribed and even unwitnessed, often displaced to another site, such as a letter or nameless voice. When politically motivated attacks committed by working-class characters are represented, these moments are mediated by an upper-middle-class spectator or translator. This paper seeks to identify and explore the presence and significance of politically motivated violence in the novel, emphasizing its centrality within the text and highlighting its connection with nineteenth-century attitudes to issues of regional dialect, the legitimacy of force and 'Yorkshire roughness'.